Al-Jinas fi Diwan li al-Imam al-Syafi’i - Supriyadi, Moh.; Murtaqi, Rizal (Dzil Majaz: Journal of Arabic Literature, 2024)
The well-known beginning of Urdu poetry in this country was in the year 1450 AD, and hundreds of poets emerged and became famous during those long periods. He received several titles from the state, and he had published collections, and others. There are famous poets such as Anis, Dabir, Hali, Akbar Allahabadi, Amjad al-Khidarabadi, and these Poets whose poetry in Urdu literature is considered an argument, and what is cited in it. There are those poets mentioned, such as: Dagh, Anis, and Dabeer. They said visuals containing five hundred pistols, or six hundred pistols, and each pistol contains three verses, and the Urdu language after this is a language that has absorbed all meanings and descriptions. the beautiful. Therefore, the researcher seeks to research this collection, and the researcher chose this research to be the topic of research in his research, and the researcher must focus his research on the science of Badi’, which had not been researched before, meaning the sensitive one in the collection of Al-Shafi’i.